2011
DOI: 10.1038/eye.2011.40
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of tonosafe disposable tonometer prisms: clinical implications from the Veterans Affairs Boston Healthcare System Quality Assurance Study

Abstract: Purpose Given the Veterans Affairs Boston Healthcare System's recent introduction of single-use Tonosafe disposable tonometer prisms as an alternative to Goldmann applanation tonometers (GATs), this study had two aims: to conduct a large-scale quality assurance trial to assess the reliability of intraocular pressure (IOP) measurements of the Tonosafe disposable tonometer compared with GAT, particularly at extremes of pressure; to evaluate the suitability of Tonosafe disposable tonometer prisms as an acceptable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…[ 36 37 ] Furthermore, other studies supported that Tonosafe ® prism is highly correlated to nondisposable GAT with comparable retest repeatability, suggesting that Tonosafe is an acceptable substitute for GAT. [ 38 39 ] The disposable tip may underestimate IOP slightly (compared with conventional Goldmann) for IOPs above 21 mmHg. [ 36 ]…”
Section: Goldmann Applanation Tonometrymentioning
confidence: 99%
See 2 more Smart Citations
“…[ 36 37 ] Furthermore, other studies supported that Tonosafe ® prism is highly correlated to nondisposable GAT with comparable retest repeatability, suggesting that Tonosafe is an acceptable substitute for GAT. [ 38 39 ] The disposable tip may underestimate IOP slightly (compared with conventional Goldmann) for IOPs above 21 mmHg. [ 36 ]…”
Section: Goldmann Applanation Tonometrymentioning
confidence: 99%
“…The increased cost of nondisposable prisms was derived from the added cost of cleaning solutions and labor involved for disinfection. [ 39 ] In contrast to most departments, the cleaning solution is routinely provided for disinfecting contact lenses and, as such, does not represent any additional cost.…”
Section: Goldmann Applanation Tonometrymentioning
confidence: 99%
See 1 more Smart Citation
“…However, there have been reports of outbreaks of epidemic viral ocular infections in ophthalmic clinics worldwide. 3–5 Epidemiological and clinical studies of epidemic keratoconjunctivitis in eye clinics have identified possible contamination with tonometer tips, eye drop bottles and contact with infected healthcare workers as vehicles of transmission (particularly of adenoviral serotypes). 6 7…”
Section: Purposementioning
confidence: 99%
“…The notion of ‘perceived safety’ and evidence showing comparable accuracy and cost between both prism heads have led to a gradual but definite shift to the use of disposable prisms worldwide. 3 4 8 9 The primary aim of this survey was to compare the use of disposable versus non-disposable prisms and to determine the cost–benefits of each in current UK practice.…”
Section: Purposementioning
confidence: 99%